A Review on Dielectric Breakdown of Anodic Oxide Films on Aluminum Alloys - Hien Van Pham(팜반히엔); Cheolnam Yang(양철남); Sungmo Moon(문성모) (Biuletyn Uniejowski, 2024)
This paper reviews the dielectric breakdown resistance and behavior of anodic oxide films in air environment. It begins with a description of the dielectric breakdown mechanisms of dielectric materials. The paper then introduces different types of dielectric materials and compares them in terms of dielectric strength, thermal conductivity, mechanical strength and cost. Next, the paper summarizes various fabrication methods for dielectric aluminum oxide layers, discussing the advantages and disadvantages of each method. Finally, it provides an overview of current studies on the dielectric breakdown properties of anodic aluminum oxide films formed on different aluminum alloys in various electrolytes. KCI Citation Count: 0